Theories and approaches of environmental economics - Joshi, M. V. (New Delhi, 2001)
With the development process, there are dangerous risks to future well-being posed by acid rain, ozone depletion and green-house effects. The time has come to study environmental degradation, its causes, effects and remedies in the economic context. Environmental economics is suitable theoretical and applied platform for this. The book is best combination of theoretical analysis of environmental problems. Here the meaning, nature, scope and importance of environmental economics are analyzed. The various theories of Sustainable Development and Environmental Impact Assessment are reviewed. An attempt has been made to examine the role of State and market in the context of environment to analyze the pollution theories and problems, environment and development, environmental industrial management and culture and environment etc. This book will very useful to environmental researchers, theorists, students, teachers and environmental institutions. This will guide to policy-makers and environmental reformers, organizers etc.
Keywords: Environment